Extracranial ultrasound following mechanical thrombectomy in patients with acute stroke. Issue 2 (14th December 2021) - Roesler, Jennifer; Haertl, Johanna; Wunderlich, Silke; Boeckh‐Behrens, Tobias; Maegerlein, Christian; Bartels, Eva; Ikenberg, Benno
Abstract: Background and Purpose: Mechanical thrombectomy (MT) is standard care for patients suffering from an ischemic stroke due to a large vessel occlusion. Immediate and follow‐up transcranial ultrasound examinations after MT were shown to have a diagnostic benefit. However, it is unclear whether repeated extracranial ultrasound after MT has an additional diagnostic yield, that is, depicts new findings. Methods: Retrospectively, from our prospective database we identified all patients after MT who presented for a follow‐up examination between January 2017 and March 2020 and who had received an ultrasound examination after MT and at follow‐up. Clinical data were extracted from our database. Ultrasound images of all patients were revisited to identify new findings at follow‐up compared to examination after MT. Results: Ninety‐one patients were identified appropriate for further analysis, with a mean age of 67.8 ± 16 years. Median National Institute of Health Stroke Scale at admission was 11 ± 8.5 points. At baseline ultrasound, 18 patients (19.8%) had no atherosclerotic alterations and 73 patients (82.2%) had a plaque burden of ≥1 plaque. During follow‐up, in 5 patients (5.5%) a pathological finding presented in first examination evolved dynamically, that is, normalized. Vessel status of all other patients was stable, especially, in no patient a new relevant pathological finding occurred. Conclusions: Although sonographic normalization of pathologic findings was observed, pathologic new findings were not detected during follow‐up. This study provides first data for a discussion of the role of ultrasound in a structured stroke care after MT. However, larger studies are required to improve the understanding.